2015
DOI: 10.1101/cshperspect.a018846
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Sites of Adult Neurogenesis in the Mammalian Brain

Abstract: Two decades after the discovery that neural stem cells (NSCs) populate some regions of the mammalian central nervous system (CNS), deep knowledge has been accumulated on their capacity to generate new neurons in the adult brain. This constitutive adult neurogenesis occurs throughout life primarily within remnants of the embryonic germinal layers known as "neurogenic sites." Nevertheless, some processes of neurogliogenesis also occur in the CNS parenchyma commonly considered as "nonneurogenic." This "noncanonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
2
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 108 publications
0
93
2
19
Order By: Relevance
“…While these observations do not rule out the possibility that OPCs can generate mature neurons, it may help explain the conclusion drawn by others that all DCX-positive cells, including those located outside of the dentate gyrus and subventricular zone, have neuronal attributes. These observations do not rule out the possibility of OPC-derived neurogenesis but they suggest additional caution to exclude other possibilities (see further discussion of this issue in Dimou and Gallo, 2015; Feliciano et al, 2015). …”
Section: Discussionmentioning
confidence: 96%
“…While these observations do not rule out the possibility that OPCs can generate mature neurons, it may help explain the conclusion drawn by others that all DCX-positive cells, including those located outside of the dentate gyrus and subventricular zone, have neuronal attributes. These observations do not rule out the possibility of OPC-derived neurogenesis but they suggest additional caution to exclude other possibilities (see further discussion of this issue in Dimou and Gallo, 2015; Feliciano et al, 2015). …”
Section: Discussionmentioning
confidence: 96%
“…Some of these findings could not be replicated in certain mammalian species, while others could not be reproduced since their first publication or have since been contradicted by subsequent studies. It is also possible that some of these findings are based on low-level, "incomplete" neurogenic processes that protracted from embryogenesis into the postnatal period (reviewed in Bonfanti and Peretto, 2011;Feliciano et al, 2015). Despite the controversies, these cortical and subcortical areas are currently classified as the "non-canonical neurogenic regions" of the healthy mammalian brain (Bonfanti, 2013;Peretto and Bonfanti, 2014;Feliciano et al, 2015).…”
Section: Neurogenesis In the Adult Mammalian Brain: A Controversial Tmentioning
confidence: 97%
“…As compared to the DG and SVZ, far fewer numbers of new neurons are generated in these regions during adulthood although better detection methods are likely needed (Gould, 2007; Arisi et al, 2012; Inta et al, 2015; Nacher and Bonfanti, 2015; Schoenfeld and Cameron, 2015). Furthermore, many questions remain about newborn neurons in these areas including their origin (local or SVZ) and functions (Shapiro et al, 2009; Lee and Blackshaw, 2012; Feliciano et al, 2015; Inta et al, 2015). Nonetheless, a growing number of studies have revealed that neurogenesis in at least some of these areas is subject to modulation by a variety of physiological and environmental factors including pregnancy, pup exposure and parenting.…”
Section: Effects Of Pregnancy Parenting and Pup Exposure On Neuromentioning
confidence: 99%